Efectos actividad física virtual en la depresión del adulto mayor en tiempos de pandemia - Gutiérrez Huamaní, Oscar (2022)
Depression is a disease that has a higher incidence in older adults. The objective is to "determine the effects of virtual physical activity on depression in older adults during the pandemic". The method used was an analytical deductive approach, with a pre-experimental pre-test and post-test design in a single sample of 22 older adults. The results showed a low level of anxiety in the pre-test at 4.5%, which increased to 31.8% in the post-test. A similar pattern was observed for depression, with a low level of 9.1% in the pre-test and 36.4% in the post-test. It was concluded that virtual physical activity has significant effects in reducing symptoms of anxiety and depression in older adults.